YouTube and intergenerational communication: the case of Geriatric1927 - Harley, Dave; Fitzpatrick, Geraldine (Universal access in the information society, 2009)
This paper presents a case study of a 79 year old video blogger called ‘Geriatric1927’, and his use of the video sharing website, YouTube. Analysis of his first eight video blogs, and the subsequent text responses, reveals opportunities of this medium for intergenerational contact, reminiscence, reciprocal learning and co-creation of content, suggesting that older people can be highly motivated to use computers for social contact. The paper concludes by noting the importance of technologies that are socially engaging and meaningful for older people, and pointing to ways in which the social life of YouTube might be better promoted on its interface.